Peran Tokoh Agama dalam Meningkatkan Solidaritas Sosial pada Jemaat Multikultural : Sebuah Kajian Normatif di Jemaat Gmit Sion Oepura - Evi Junaidy Naitboho; Aelsthri Ndandara; Jacklin Stefany Manafe; Hotlif A. Nope (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is motivated by the reality of ethnic and cultural diversity in congregation life which reflects the dynamics of a multicultural society, where differences in cultural identity have the potential to cause social friction if not managed wisely. This research uses a descriptive qualitative approach with normative studies, with data collection techniques through interviews, observations, and documentation of informants consisting of pastors, congregation councils, and presbyters. The theory used is Ralph Linton's role theory which explains how individuals carry out social functions according to their status in society. The results of the study indicate that the life of the GMIT Sion Oepura congregation is characterized by multicultural dynamics as seen from the diversity of ethnicities such as Timor, Rote, Sabu, Flores, and Alor which not only enriches church life through cultural expressions in worship and church activities, but also gives rise to symbolic friction between ethnic groups, such as the tendency for the dominance of certain cultural symbols and the emergence of group ego attitudes in several worship activities, for example in the celebration of Language and Culture Month. In this situation, religious leaders play a role as leaders who embrace diversity, mediators in managing potential conflicts, and social and moral role models for the congregation through sermons, pastoral guidance, and various service activities that involve the entire congregation without differentiating cultural backgrounds. Despite the existence of cultural differences and the tendency for certain symbolic dominance, religious leaders are able to manage this diversity normatively so that it does not develop into open conflict. This study concludes that the role of religious leaders is very important in strengthening social solidarity and maintaining harmony in multicultural congregations.